EVALUASI PEMBANGUNAN PERUMAHAN - Taufik Dwi Laksono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2006)
AbstraksiDeveloper before executing housing development shall conduct the matured evaluation so that housing developed can be enthused and saleable of marketable, because without matured evaluation non housing not possible to be the is not saleable sold. Procedure which is a lot of developed is how far marketable project, elegibility goodness technically and its profitability. Therefore to determine the commercialisation potency, hence must be done three type evaluate namely evaluate the marketing to determine the commercial potency request, evaluate the technical worthiness to determine the technological performance, and evaluate the profitability to determine the advantage finansial and economic.Â Keyword: developer, housing, evaluate